Pengaruh Sumber Daya Yang Unik, Kepemimpinan, Penerapan Efisiensi, Terhadap Peningkatan Kerja Di Mediasi Motivasi dan Di Moderasi Umur: Literature Review - Sangapan, Lukman; Carlos, Gerry Juan; Manurung, Adler Haymans; Manurung, John Sihar (OGZ Research & Publishing, 2025)
Abstract : This study also opens up space for further quantitative data-based studies to examine the relationship between variables in greater depth. Objective : This study aims to examine the influence of unique resources, leadership, and efficiency on organizational performance improvement, considering the mediating role of work motivation and the moderating role of age. Method : This study was conducted using a systematic literature review approach on ten selected academic articles relevant to the research theme. Data were analyzed using thematic content analysis techniques and presented in the form of narratives, tables, and quotations from the original sources. Results : The research findings indicate that unique resources, strategic leadership, and efficiency have a positive relationship with organizational performance. Work motivation was found to to be a significant mediator in strengthening this relationship. Meanwhile, age as a moderator variable showed varying influences based on workforce generation groups. These findings contribute significantly to the development of human resource management theory and organizational practices that are more contextual and adaptive.